2015
DOI: 10.1001/jama.2015.14849
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Myocardial Scar in a US Cohort

Abstract: Importance Myocardial scarring leads to cardiac dysfunction and poor prognosis. The prevalence of and factors associated with unrecognized myocardial infarction and scar have not been previously defined using current methods in a multi-ethnic US population. Objective To determine prevalence of and factors associated with myocardial scar in middle and older aged individuals in the United States (U.S). Design, Setting, and Participants Multi-Ethnic Study of Atherosclerosis (MESA) is a population based cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 32 publications
5
87
3
3
Order By: Relevance
“…This rigorous screening allowed us to better isolate the effect of exercise training per se, from the confounding effects of other co-morbidities. In fact, the prevalence of LGE in the present cohort was lower than reported in the general population, 34 likely due to the absence of cardiovascular disease risk factors. The lack of association of lifelong high endurance exercise with areas of focal myocardial fibrosis, especially in individuals with youthfully compliant hearts as assessed directly by invasive measures lends support to the concept that the ‘athlete's heart’ is most commonly a reversible physiological adaptation and not a pathological substrate for malignant arrhythmias or a precursor to cardiovascular death.…”
Section: Discussioncontrasting
confidence: 84%
“…This rigorous screening allowed us to better isolate the effect of exercise training per se, from the confounding effects of other co-morbidities. In fact, the prevalence of LGE in the present cohort was lower than reported in the general population, 34 likely due to the absence of cardiovascular disease risk factors. The lack of association of lifelong high endurance exercise with areas of focal myocardial fibrosis, especially in individuals with youthfully compliant hearts as assessed directly by invasive measures lends support to the concept that the ‘athlete's heart’ is most commonly a reversible physiological adaptation and not a pathological substrate for malignant arrhythmias or a precursor to cardiovascular death.…”
Section: Discussioncontrasting
confidence: 84%
“…27 More recently, in the MESA study, unrecognized scar was reported in 6.2% of participants of whom 62% were classified as “atypical” for myocardial infarction. 18 The prevalence of scar in the current study was slightly different from the prior publication as individuals with an incident HF event prior to exam 5 were excluded in the present analysis. The lower prevalence of LGE, and particularly “typical” scar compared with prior non-MESA general population studies is likely based on the initial exclusion in MESA of known CVD, the race/ethnic heterogeneity of the cohort (with whites having the highest prevalence of LGE) and younger age of MESA participants.…”
Section: Discussionmentioning
confidence: 74%
“…Myocardial scars predominantly affecting midwall or subepicardium without subendocardial involvement in a non-coronary artery distribution were defined as an “atypical” scar. 18 …”
Section: Methodsmentioning
confidence: 99%
“…), 146 (7,9 %) osoba imalo je ožiljke miokarda. 27 U 78 % osoba ožiljci miokarda nisu bili prepoznati elektrokardiogramom ni kliničkom evaluacijom. Dob, muški spol, indeks tjelesne mase, arterijska hipertenzija i vrijednost CACS-a (prilagođena spolu, dobi i etničkoj skupini) pri prvom pregledu povezani su s prisutnošću ožiljaka miokarda nakon 10 godina.…”
Section: Cardiovascular Magnetic Resonanceunclassified
“…30 Ispitanici s ranom prezentacijom dilatacijske kardiomiopatije, s obzirom na ispitanike koji se bave aerobnim aktivnostima više od 6 sati na dan, pokazali su znatno produženje participants in the MESA study who were free of clinical cardiovascular disease at baseline (in 2000-2002) and underwent LGE CMR in the 10 th year examination (2010-2012), 146 (7.9%) individuals showed myocardial scar. 27 In 78% of them, myocardial scar was unrecognized by electrocardiogram or clinical evaluation. Age, male sex, body mass index, hypertension, and CACS (adjusted for age, sex, and ethnicity) at baseline were associated with presence of myocardial scar at year 10.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 99%